Study the Possibility of using Ground-Penetrating Radar to Detect Walls and Archaeological Finds underground - S. Mahdi, Alaa; A.Mohammed, Anas (Iraqi Journal of Science, 2023)
Ground penetrating radar (GPR) is one of the geophysical methods that utilize electromagnetic waves in the detection of subjects below the surface to record relative position and shape of archaeological features in 2D and 3D. GPR method was applied in detecting buried archaeological structure in study area in a location within the University of Baghdad. GPR with 3D interpretation managed to locate buried objects at the depth of (1m) . GPR Survey has been carried (12) vertical lines and (5) horizontal lines using frequency antenna (500) MHZ .